2017
DOI: 10.7596/taksad.v6i5.1310
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Regional University Development in Modern Russia

Abstract: The article describes the determinants that are manifested in regional social-economic complexes and determine the main trends of development and educational activities for regional universities. The authors determined and characterized such determinants as social-economic (or financial, and infrastructural) uneven development of Russia; the economic mechanism of higher education economic accessibility stratification; the need to equalize the professional educational network in the regions of Russia to ensure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…It was also revealed that at present, large regional universities, such as, for example, federal and flagship universities, project themselves as high-tech educational organizations, focusing primarily on the regional and, in many ways, diversified market of educational and research services (Gonik et al, 2016;Bachiev, 2017;Ameen et al, 2018).…”
Section: Results and Its Discussionmentioning
confidence: 99%
“…It was also revealed that at present, large regional universities, such as, for example, federal and flagship universities, project themselves as high-tech educational organizations, focusing primarily on the regional and, in many ways, diversified market of educational and research services (Gonik et al, 2016;Bachiev, 2017;Ameen et al, 2018).…”
Section: Results and Its Discussionmentioning
confidence: 99%
“…The establishment of a flagship university will contribute to intellectual resources promotion in the mobilization scenario of the regional development, to a profound qualitative change of its role in the development of the global competitiveness of the region, and the improvement of the living standards of the population (Bachiev et al, 2017;Malganova et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, federal and flagship universities are prognostic models of new regional high-tech educational organizations that should become drivers of regional development (Markaryan, Bachiev et al, 2017), or regional determinants of socio-economic development. Our point of view is that the driver of all changes in the region should be an innovative person -a category meaning that every teacher, student, graduate of a regional university should become adaptive to permanent changes -in their own life, in economic and cultural development, in development of science and technology -an active initiator and producer of these changes with projective or "design-thinking" (Kotova, Mitusova, Gelpey, 2018).…”
Section: Introductionmentioning
confidence: 99%